Pollen contamination in seed mixture increases the dominance of resistance to Bt maize in Spodoptera frugiperda (Lepidoptera: Noctuidae). Issue 11 (23rd August 2017) - Yang, Fei; Kerns, David L; Brown, Sebe; Head, Graham P; Huang, Fangneng
Abstract: BACKGROUND: Seed mixture, also called 'RIB', has been used to provide refuge populations for delaying insect resistance. Pollen contamination in RIB could result in refuge kernels of non‐Bt maize expressing variable Bt proteins. Data are lacking regarding the impact of pollen contamination on evolution of resistance for ear‐feeding insects. Here, we used Spodoptera frugiperda and Cry1F‐maize as a model to examine if pollen contamination in RIB increases the dominance of insect resistance. RESULTS: Pollen contamination caused >66% refuge kernels in 5:95% (non‐Bt:Bt) and 20:80% RIBs to express Cry1F protein. Survival at adult stage on pure non‐Bt ears was similar (54.4–63.3%) among Cry1F‐susceptible (SS), Cry1F‐resistant (RR) and Cry1F‐heterozygous (RS) S. frugiperda . On Bt ears, survival was similar between SS and RS (0.0–1.7%), but it was significantly less than that of RR (59.2%). On the two RIB refuge ears, survival at adult stage for RS (42.3% in 5:95% RIB; 50.0% in 20:80% RIB) was significantly higher than for SS (8.7% in 5:95% RIB; 10.0% in 20:80% RIB). CONCLUSION: The results suggest that pollen contamination in RIB could increase the dominance of resistance for ear‐feeding insects by significantly reducing susceptible refuge populations and supporting higher survival of heterozygotes relative to homozygous susceptible insects. © 2017 Society of Chemical Industry